Schisandrin B prevents ulcerative colitis and colitis-associated-cancer by activating focal adhesion kinase and influence on gut microbiota in an in vivo and in vitro model - Li, Jiani; Lu, Yuan; Wang, Duowei; Quan, Fei; Chen, Xin; Sun, Rui; Zhao, Sen; Yang, Zhisen; Tao, Weiyan; Ding, Dong; Gao, Xinghua; Cao, Qiuhua; et al. (European journal of pharmacology, 2019)
Colitis-associated cancer (CAC) has a close relationship with ulcerative colitis (UC). Therapeutic effect of Schisandrin B (SchB) on UC and CAC remains largely unknown. We investigated the preventative effect of SchB on the dextran sulphate sodium (DSS) model of UC and azoxymethane (AOM)/DSS model of CAC. Furthermore, focal adhesion kinase (FAK) activation and influence on commensal microbiota are important for UC treatment. Impact on FAK activation by SchB in UC development was evaluated in vivo and vitro. We also conducted 16S rRNA sequencing to detect regulation of gut microbiota by SchB. Enhanced protection of intestinal epithelial barrier by SchB through activating FAK contributed to protective effect on colon for the fact that protection of SchB can be reversed by inhibition of FAK phosphorylation. Furthermore, influence on gut microbiota by SchB also played a significant role in UC prevention. Our results revealed that SchB was potent to prevent UC by enhancing protection of intestinal epithelial barrier and influence on gut microbiota, which led to inhibition of CAC. SchB was potential to become a new treatment for UC and prevention of CAC. [Display omitted]